The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/1519-6984.234129
|View full text |Cite
|
Sign up to set email alerts
|

Linking fish and crustacean taxonomic composition with seasonal contrasts in the soft-bottom intertidal zone

Abstract: The primary objective of this study was to investigate the seasonal fish and crustacean variations concerning taxonomic composition, species richness, and diversity in sandy beach habitat. For this purpose, we investigated the Sonmiani Hor lagoon area during four distinct seasons, i.e., northeast (NE) monsoon, pre-monsoon, south-west (SW) monsoon, and post-monsoon for one year. During each haul, the net was pulled about 100m along the beach in 0.5m depth. The results showed a strong linear correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Krykhtina et al (2021) revealed temperature as a crucial environmental factor for the survival of aquatic organisms, particularly crustaceans, because this parameter affects their metabolism and reproduction processes. Additionally, climate can contribute to the survival of crustaceans due to their most abundant in waters during the rainy season (Wahyudin et al 2017;Hamid and Wardiatno 2018;Shields 2019;Gondal et al 2021;Muhtadi et al 2022). One of the diversity of crustaceans in the waters of Teluk Mengkudu is fishermen who sail at night using trawls which can damage coral reefs.…”
Section: Dominance Index (D)mentioning
confidence: 99%
“…Krykhtina et al (2021) revealed temperature as a crucial environmental factor for the survival of aquatic organisms, particularly crustaceans, because this parameter affects their metabolism and reproduction processes. Additionally, climate can contribute to the survival of crustaceans due to their most abundant in waters during the rainy season (Wahyudin et al 2017;Hamid and Wardiatno 2018;Shields 2019;Gondal et al 2021;Muhtadi et al 2022). One of the diversity of crustaceans in the waters of Teluk Mengkudu is fishermen who sail at night using trawls which can damage coral reefs.…”
Section: Dominance Index (D)mentioning
confidence: 99%
“…Changes in dietary preferences of a fish species largely depend on the availability of preferred prey items in the associated environment. An abundance of favorite prey items in the environment regulates their predominance of food items in the fish stomach (Palmeira and Monteiro-Neto, 2010;Gondal et al, 2020;Kim et al, 2021). Moreover, energy requirements by fish in a specific phase of life sometimes induce ontogenetic shifts in dietary mode and selectivity (Cruz Escalona and Abitia Cárdenas, 2004).…”
Section: Introductionmentioning
confidence: 99%